2015
DOI: 10.1017/s1092852915000759
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the treatment of binge eating disorder

Abstract: We performed a qualitative review of treatment studies of binge eating disorder (BED), focusing on randomized clinical trials (RCTs). Limited effectiveness has been demonstrated for self-help strategies, and substantial effectiveness has been shown for cognitive behavioral therapy (CBT) and interpersonal therapy (IPT). CBT and IPT may each be more effective than behavior weight loss therapy (BWLT) for reducing binge eating over the long term. The stimulant pro-drug lisdexamfetamine dimesylate (LDX) is the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
12

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 100 publications
2
57
0
12
Order By: Relevance
“…This meta-analysis concur with a review by McElroy et al [16] for the effectiveness of CBT in reducing binge eating frequency in the short-term, but do not support their more supportive findings in the longer-term . Although BWLT showed greater effects for weight loss at the end of treatment in comparison to CBT in three trials [17,30,34], no significant differences were found between these interventions in meta-analyses, in either the short or long term.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…This meta-analysis concur with a review by McElroy et al [16] for the effectiveness of CBT in reducing binge eating frequency in the short-term, but do not support their more supportive findings in the longer-term . Although BWLT showed greater effects for weight loss at the end of treatment in comparison to CBT in three trials [17,30,34], no significant differences were found between these interventions in meta-analyses, in either the short or long term.…”
Section: Discussionsupporting
confidence: 48%
“…A further systematic review reported that even very low calorie diets may be beneficial for individuals with BED [15]. Another recent review found CBT and Interpersonal Therapy (IPT) to be the most effective treatments for binge eating reduction over the short and long term for patients with BED [16]. However, these last two approaches do not target weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…4,8,10,11 To manage psychotic, depressive, and manic symptoms, schizoaffective disorder is treated with complex pharmacologic regimens that include antipsychotics, mood stabilizers, and antidepressants. [12][13][14] Only oral paliperidone, administered as monotherapy or adjunctively with mood stabilizers and/or antidepressants, has received regulatory approval for acute treatment of schizoaffective disorder [5][6][7]15 ; however, no widely accepted clinical guidelines for acute or maintenance treatment exist.…”
mentioning
confidence: 99%
“…As patients with mood disorder and obesity have high rates of binge eating behavior, it is important to be aware of the growing number of pharmacological agents efficacious for BED or BN (see Table 3) [125,126]. These drugs include antidepressants, lisdexamfetamine, and the antiepileptic drugs topiramate and zonisamide.…”
Section: Pharmacotherapy Of Binge Eatingmentioning
confidence: 99%